Modelling and experimental validation of dynamic impact in 1:9 railway crossing panel. (February 2018) - Ma, Yuewei; Mashal, Abdul Ahad; Markine, Valeri L.
Abstract: To improve the understanding of dynamic impact in 1:9 crossing panel, which is suffering from rapid surface degradation, detailed modelling and experimental studies are performed. A three-dimensional explicit finite element (FE) model of a wheel rolling over a crossing rail, that has an adaptive mesh refinement procedure coupled with two-dimensional geometrical contact analyses, is developed. It is demonstrated that this modelling strategy performs much better than the 'conventional' FE modelling approach. Also, the experimental validations show that the FE results agree reasonably well with the field measurements. Using the validated FE model, the tribological behaviour of contact surfaces is studied. The results indicate that the proposed modelling strategy is a promising tool for addressing the problems of wheel-crossing dynamic impact. Highlights: A three dimensional (3D) finite element (FE) model of a wheel rolling over a crossing rail is developed. The effectiveness of the presented modelling strategy is demonstrated in comparison to the conventional FE model. The accuracy of FE simulations is validated against field measurements. The influence of impact phenomena on the tribological behaviour of contact surfaces/subsurface is studied.